Efektivitas Media Pembelajaran Audio Visual pada Mata Pelajaran PKN Terhadap Hasil Belajar Siswa Sekolah Dasar (International Forum of Researchers and Lecturers, 2024)
Audio-visual media commonly used in teaching and learning activities in the 21st century. The purpose of this research is to determine how effective audio-visual media is to be applied in elementary schools to improve student learning outcomes in Civics subjects in Elementary Schools. By using qualitative method with a literature study approach. The form of activity carried out is to conduct literature research through collecting data with listening techniques, participatory observation taken from Google Scholar with the keywords